2020
DOI: 10.1186/s13071-020-04047-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of differentially expressed profiles of mRNAs, lncRNAs and circRNAs in chickens during Eimeria necatrix infection

Abstract: Background: Eimeria necatrix, the most highly pathogenic coccidian in chicken small intestines, can cause high morbidity and mortality in susceptible birds and devastating economic losses in poultry production, but the underlying molecular mechanisms in interaction between chicken and E. necatrix are not entirely revealed. Accumulating evidence shows that the long-non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) are key regulators in various infectious diseases. However, the expression profiles and roles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 126 publications
1
14
0
Order By: Relevance
“…(2020) reported that 27 differentially expressed circRNAs were involved in the immune response to infectious bursal infection in chickens. Fan et al. (2020) performed transcriptome sequencing on the small intestine tissues of chickens infected with E. necatrix .…”
Section: Discussionmentioning
confidence: 99%
“…(2020) reported that 27 differentially expressed circRNAs were involved in the immune response to infectious bursal infection in chickens. Fan et al. (2020) performed transcriptome sequencing on the small intestine tissues of chickens infected with E. necatrix .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, circRNAs, a novel RNA class, are being recognized to function in many kinds of physiological and pathological processes by regulating gene expression at the transcriptional and posttranscriptional levels [ 34 36 ]. Significantly aberrant expression of host circRNAs at the genome-wide level was also found during infections with a limited number of parasites [ 13 , 18 , 37 ], including Cryptosporidium [ 19 ]; however, the functions of these DE circRNAs are still unknown. In the present study, we performed microarray analysis of DE circRNAs in HCT-8 cells infected with the important zoonotic C. parvum and identified a total of 178 circRNAs (including 128 upregulated and 50 downregulated) that were abnormally expressed.…”
Section: Discussionmentioning
confidence: 99%
“…porcine endemic diarrhea virus, transmissible gastroenteritis virus), and parasites (e.g. Nosema ceranae , Toxoplasma gondii , Eimeria necatrix ) [ 13 18 ]. Using the RNA-seq technique without RNase R treatment, our group found 104 significantly differentially expressed circRNAs in tracheal tissues of chickens experimentally infected with C. baileyi .…”
Section: Introductionmentioning
confidence: 99%
“…One RNA sequence analysis of differentially expressed lncRNAs, circRNAs, and mRNAs has been performed in chicken small intestines during Eimeria necatrix infection. This RNA sequence analysis obtained 1543 DEmRNAs, 95 DElncRNAs, 13 DEcircRNAs [144]. Functional annotation for lncRNAs, miRNAs, and circRNAs were correlated with chicken host immune defense and pathogenesis during E. necatrix infection [144].…”
Section: Ncrnas Associated With Coccidiosis and Cryptosporidium Bailementioning
confidence: 97%
“…This RNA sequence analysis obtained 1543 DEmRNAs, 95 DElncRNAs, 13 DEcircRNAs [144]. Functional annotation for lncRNAs, miRNAs, and circRNAs were correlated with chicken host immune defense and pathogenesis during E. necatrix infection [144]. In addition, miRNA expression was compared between naturally or Eimeria maxima and Eimeria acervulina -infected Ross 308 broilers using RNA sequencing.…”
Section: Ncrnas Associated With Coccidiosis and Cryptosporidium Bailementioning
confidence: 99%